Differentiation of athlete's heart from pathological forms of cardiac hypertrophy by means of geometric indices derived from cardiovascular magnetic resonance. - Petersen, SE; Selvanayagam, J; Francis, J; Myerson, S; Wiesmann, F; Robson, M; Ostman-Smith, I; Casadei, B; Watkins, H; Neubauer, S (2005)
PURPOSE: Determination of the underlying etiology of left ventricular hypertrophy (LVH) is a common, challenging, and critical clinical problem. The authors aimed to test whether pathological LVH, such as occurs in hypertrophic cardiomyopathy (HCM), hypertensive heart disease, or aortic stenosis, and physiological LVH in athletes, can be distinguished by means of left ventricular volume and geometric indices, derived from cardiovascular magnetic resonance imaging. METHODS: A total of 120 subjects were studied on a 1.5 Tesla MR (Sonata, Siemens Medical Solutions, Erlangen, Germany) scanner, comprising healthy volunteers (18), competitive athletes (25), patients with HCM (35), aortic stenosis (24), and hypertensive heart disease (18). Left ventricular mass index, ejection fraction, end-diastolic, end-systolic and stroke volume index, diastolic wall thickness, wall thickness ratio and diastolic and systolic wall-to-volume ratios were determined. RESULTS: Left ventricular (LV) mass indices were similar for all forms of LVH (p > 0.05), which were at least 35% higher than those obtained in healthy volunteers (p < 0.05). Multiple logistic regression showed that the percentage of correctly predicted diagnoses was 100% for athlete's heart, 80% for hypertrophic cardiomyopathy, 54% for aortic stenosis, and 22% for hypertensive heart disease. Using a receiver operating curve-determined cut-off value for diastolic wall-to-volume ratio of less than 0.15 mm x m2 x ml(-1), athletes' hearts could be differentiated from all forms of pathological cardiac hypertrophy with 99% specificity. CONCLUSIONS: Athlete's heart can be reliably distinguished from all forms of pathological cardiac hypertrophy using CMR-derived LV volume and geometric indices, but pathological forms of LVH present with overlapping cardiac hypertrophy phenotypes. This capability of CMR should be of high clinical value.